Comparison of design, metallurgy, mechanical performance and shaping ability of replica‐like and counterfeit instruments of the ProTaper Next system. (10th January 2021) - Martins, J. N. R.; Silva, E. J. N. L.; Marques, D.; Belladonna, F.; Simões‐Carvalho, M.; Camacho, E.; Braz Fernandes, F. M.; Versiani, M. A.
Abstract: Aim: To compare the ProTaper Next (PTN) system with a replica‐like and a counterfeit system regarding design, metallurgy, mechanical performance and shaping ability. Methodology: Replica‐like (X‐File) and counterfeit (PTN‐CF) instruments were compared to the PTN system regarding design (microscopy), phase transformation temperatures (differential scanning calorimetry), nickel‐titanium ratio (energy‐dispersive X‐ray spectroscopy), cyclic fatigue, torsional resistance, bending strength, and untouched canal areas in extracted mandibular molars (micro‐CT). anova, post hoc Tukey's and Kruskal–Wallis tests were used according to normality assessment (Shapiro–Wilk test) with the significance level set at 5%. Results: Overall similarities in design and nickel‐titanium (Ni/Ti) ratio were observed amongst instruments with the X‐File having a smoother surface finish. PTN and PTN‐CF had mixed austenite plus R‐phase (R‐phase start approximately at 45 ºC and near 30 ºC, respectively), whilst X‐File instruments were austenitic (R‐phase started at approximately at 17 ºC) at room temperature (20 ºC). PTN‐CF had the greatest inconsistency in the phase transformation temperatures. Time to fracture of PTN‐CF X2 and X3 was significantly shorter than PTN and X‐File instruments ( P  < 0.05), whilst no difference was noted in maximum torque to fracture amongst the tested systems ( P  > 0.05). X‐Files and PTN‐CF had a stress‐induced phase change during bending load. Mean unprepared surface areas of root canals were 25.8% (PTN), 31.1% (X‐File) and 32.5% (PTN‐CF) with no significant difference amongst groups ( P  > 0.05). Conclusion: Similarities amongst the systems were noted in the Ni/Ti ratio and maximum torque to fracture, whilst differences were observed in the design, phase transformation temperatures and mechanical behaviour. The ProTaper Next counterfeit instruments could be considered as the less secure system considering its low‐cyclic fatigue resistance. Apart from these differences, the unprepared canal surface areas, obtained with the tested systems, were similar.